Determinants of handwashing behaviour among primary school teachers in a district of Ghana - Samson Gbolu; Emmanuel Appiah-Brempong; Paul Okyere; Hasehni Vampere; Gloria Obeng Nyarko; Kofi Akohene Mensah (Health Psychology and Behavioral Medicine, 2023)
ABSTRACTBackground: Hand hygiene practise is an effective school-based measure for infectious disease prevention, especially in developing countries. School children model their behaviour through the observation of significant others, including teachers. However, little is known about the handwashing behaviour and factors influencing the handwashing practises of teachers at the primary school level in Ghana.Methods: A quantitative cross-sectional study was conducted among 214 primary school teachers, recruited by convenience sampling. Data were collected using a structured questionnaire which were designed based on selected constructs in the Theory of Planned Behaviour and the Health Belief Model. Data analyses was done with the aid of STATA software, version 14.0. To identify determinants of hand washing with soap (HWWS) among participants, correlation and multiple linear regression analysis were used.Results: The participants’ mean SD age was 34.7 7.6 years, ranging from 20 to 51 years. The majority were males (87.9%). The majority (84.0% and 86.0%) of the teachers, respectively, reported HWWS practises after using the toilet and before eating with bare hands. A correlation was found between reported HWWS practise and toilet use (r = 0.64; p = 0.001) and eating with bare hands (r = 0.84; p = 0.001). A multiple linear regression analysis found that knowledge (p = 0.001), attitude toward HWWS (p = 0.002), and teachers’ perception of the severity of diarrhoea (p = 0.009) were determinants of teachers’ reported HWWS behaviours.Conclusion: Teachers’ perceptions of their susceptibility to and severity of diarrhoea, and their knowledge and attitude towards HWWS at critical times should be focus areas for handwashing programmes to achieve the desired outcomes.